2022
DOI: 10.1021/jacs.2c07972
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Magic-Size Clusters via Precursor Compound Cation Exchange at Room Temperature

Abstract: The transformation of colloidal semiconductor magic-size clusters (MSCs) from zinc to cadmium chalcogenide (ZnE to CdE) at low temperatures has received scant attention. Here, we report the first room-temperature evolution of CdE MSCs from ZnE samples and our interpretation of the transformation pathway. We show that when prenucleation stage samples of ZnE are mixed with cadmium oleate (Cd­(OA)2), CdE MSCs evolve; without this mixing, ZnE MSCs develop. When ZnE MSCs and Cd­(OA)2 are mixed, CdE MSCs also form. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 60 publications
1
68
0
Order By: Relevance
“…With the inductive effect, the electron density of the a carbon atom decreases as well but to a smaller degree. The spectrum line width of the d carbon atom in trace 1 is larger than that in trace 2, suggesting a smaller relaxation time T 2 , 21,27,33 that can be attributed to a slower motion of a larger species (MSC) and the chemical exchange among various species such as the bonded and free PhOH molecules.…”
Section: ■ Nmr Study For the Interaction Between Phoh And Msc-399mentioning
confidence: 98%
See 1 more Smart Citation
“…With the inductive effect, the electron density of the a carbon atom decreases as well but to a smaller degree. The spectrum line width of the d carbon atom in trace 1 is larger than that in trace 2, suggesting a smaller relaxation time T 2 , 21,27,33 that can be attributed to a slower motion of a larger species (MSC) and the chemical exchange among various species such as the bonded and free PhOH molecules.…”
Section: ■ Nmr Study For the Interaction Between Phoh And Msc-399mentioning
confidence: 98%
“…Research on MSCs is still in an early stage, ,,, and transformation of MSCs via isomerization has received marginal attention with fundamental questions unaddressed such as how MSCs isomerize under external stimuli of chemicals. Being precise in composition at the atomic level, MSCs can be considered to be analogous to organic molecules as well. The reactions that chemically transform the QDs have similarities with traditional organic reactions, although isomerization is not addressed .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al elucidated the role of the InAs-cluster-based SSP in synthesizing large InAs QDs (>9 nm) . A two-step nucleation of group II–VI MSCs (e.g., CdS) was reported, in which, under certain conditions, MSC pre-nucleation clusters (named precursor compounds or PCs) first formed and transformed into MSCs of a similar core composition. It was shown that the fragmentation of CdS PCs leads to the nucleation and growth of small-size CdS QDs with enhanced particle yield …”
Section: Introductionmentioning
confidence: 99%
“…Robinson and co-workers reported a concentration-dependent relationship in CdS MSCs. They showed that, at high concentration, high-purity clusters were obtained, while at low concentration, clusters tended to form nanocrystals. Yu and co-workers synthesized several CdS MSCs by a two-step method and demonstrated that these CdS MSCs were obtained based on the two-pathway model, where the intermediates were initially formed at a high temperature and then converted to MSCs at a relatively low temperature. , However, these CdS MSCs were difficult to isolate, and studies on the transformation mechanism in the cluster region were limited to clusters with the same composition. ,, Recently, Yu and co-workers reported the cation exchange reaction during the prenucleation stage, but the transformation of semiconductor MSCs with different anions has not yet been reported . In addition, the specific compositions of stoichiometric CdS MSCs remained unavailable, which limited the use of such MSCs as molecular inks or next-generation precursors for low-cost semiconductor fabrication. , Therefore, there is an urgent need to obtain CdS clusters with a single-sized stoichiometry and to investigate the transformation pathways in the cluster region.…”
Section: Introductionmentioning
confidence: 99%
“…11,26,27 Recently, Yu and co-workers reported the cation exchange reaction during the prenucleation stage, but the transformation of semiconductor MSCs with different anions has not yet been reported. 28 In addition, the specific compositions of stoichiometric CdS MSCs remained unavailable, which limited the use of such MSCs as molecular inks or next-generation precursors for low-cost semiconductor fabrication. 29,30 Therefore, there is an urgent need to obtain CdS clusters with a single-sized stoichiometry and to investigate the transformation pathways in the cluster region.…”
Section: ■ Introductionmentioning
confidence: 99%